Children of the Anthropocene in Urban Places and Their Learning with the Milieu - Kairė, Sandra (Problemos, 2025)
This paper aims to move from a theoretical towards the practical possibility of grasping how learning with the Milieu emerges from children’s and young people’s perspectives as they live and learn primarily in urbanized places. The potential for learning in urbanized environments as Milieus is revealed by examining specific learning experiences in two different contexts: in Lithuanian educational institutions, where children learn through a phenomenon-based methodology, and in cases where children and young people engage in climate activism outside formal education settings. The children’s and youths’ experiences of being and/or learning in urbanized environments demonstrate that they are directly connected to them as milieus. Learning within these environments potentially becomes an opportunity for active, affective engagement, creativity, and the development of equal relationships with everything that surrounds them (human and nonhuman) within and beyond specific urban places. Furthermore, an urbanized place as a milieu allows children and young people to connect with and expand their awareness of the world beyond their immediate surroundings. The paper also highlights different conditions necessary for urbanized places to become learning environments with the milieu possibility.